Misreading the Sacred? A Netnographic Analysis of Youth Reception of Arabic Songs in Shalawat Majlis - Rinda Eka Mulyani; Nida Husniah Ramadhani; Abdullah, Muhammad Yahya; Iqlima Aristania Rada (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Social media has become a platform for forming virtual communities based on shared interests, including religious expression. It also serves as a forum for exchanging ideas, often leading to the development of distinct online cultures without direct interaction. Netnography, a digital adaptation of ethnography, provides a framework for studying these cultural phenomena. This study examines how shalawat (praise for the Prophet) is shared via social media and how some Arabic love songs are mistakenly perceived as shalawat by online audiences. The research aims to analyze netizens’ responses to these songs and to explore the semantic content of the lyrics to clarify their meaning. Using a qualitative approach with a netnographic method, data were collected through online observation, interviews, and documentation. The study followed five stages: developing the research framework, selecting the object, collecting data, analyzing findings, and reporting results. The findings indicate that some users misunderstand the lyrics of Arabic love songs featured in majlis shalawat settings, assuming them to be religious chants. Semantic analysis was conducted to distinguish between love-themed lyrics and genuine shalawat, shedding light on how religious expression and popular culture may intersect and be misinterpreted in digital spaces.